CO-COMPOSTING LIMBAH PADAT BELTPRESS DAN JERAMI PADI DENGAN AERATED STATIC PILE (Jurnal Teknologi Industri Pertanian, 2017)
Solid  waste from beltpress machine in wastewater treatment plant is produced as much as 1,25 tons/day but hasnot been utilized, causing unpleasant odour and requires a high cost for disposal. Composting is one of alternative technology that can be applied to solve the problem. The objectives of this research were to examine the influence of the initial C/N value and aeration rate to the rate of co-composting process in reaching the C/N value that corresponds to SNI 19-7030-2004, and to characterize the compost produced. The research design used was factorial Complete Random Design (CRD) with two factors and two repetitions. The first factor was C/N value, consisted of 25; 30; 35 and the second factor was aeration rate, consisted of 0; 0,4; 0,8 L/min.kg of dry material. Composting was done using 30 L reactor by giving active intermittent aeration for 1 hour/day during the first 7 days of composting. Effects of initial C/N value and aeration rate were significantly different (P0.05) on pH value. Lower initial C/N value and higher aeration rate attained standard C/N value fastest. The best treatment based on the conformity with SNI 19-7030-2004 was initial C/N25 with aeration rate 0,8 L/minute.kg dry matter. The compost produced met the SNI standards in macro elements, trace elements,and other elements, but didnot qualify the pH value and moisture content.Keywords: aerated static pile, beltpress solid waste, co-composting, rice straw